P‐122: Mechanical Bending Test of High Mobility ZnO TFTs on PI Substrate by Spray Pyrolysis. Issue 1 (25th September 2020) - Saha, Jewel Kumer; Bukke, Ravindra Naik; Hasan, Md. Mehedi; Kim, Youn Goo; Islam, Md Mobaidul; Mude, Narendra Naik; Billah, Mohammad Masum; Lee, Suhui; Jang, Jin
Abstract : We study the effect of mechanical bending on electrical characteristics of flexible ZnO TFTs by spray pyrolysis having μSAT of 11.45 cm 2 /V.s on PI substrate at 350 °C. The flexible ZnO TFTs exhibit robust electrical characteristics (|ΔVTH |=0.6V) under mechanical‐strain up to 1% and even after repetitive bending for 10 4 cycles (|ΔVTH |=0.33V).